Graphene–tungsten oxide hybrid nanocomposites for high-performance dielectric films in conductive polymer matrices - Abdulwahhab H. Majeed; Wasan Abdulfatah Hussen; Ahmed Najem Abd; Zaid H. Mahmoud; Ehsan kianfar (South African Journal of Chemical Engineering)
Nanocomposite based on tungsten oxide (WO3), graphene oxide (GO), and poly (anthranilic acid) were synthesized and doped into epoxy resin film. Nanocomposite with varying WO3 content (GO-10 %WO3, GO-20 %WO3, and GO-30 %WO3) were blended with epoxy-PANA to produce hybrid films. The structural and morphological features were investigated by FTIR, XRD, EDX, and SEM. The dielectric properties including (real dielectric constant (real permittivity) (ε′), imaginary dielectric constant (imaginary permittivity) (ε″), loss factor (tanδ), and electrical conductivity (σ ac)) were evaluated across frequency of 100 kHz to 5 MHz. All prepared films appeared reducing in ε′, ε″ and tan δ with increasing frequency, while (σ ac) increased. Notably, higher WO3 loading improvement both permittivity and conductivity, with GO-30 %WO3/epoxy-PANA appearing the most significant improvement. These results highlight the potential of prepared composite in dielectric and conductive applications.